Genetic variability in Indian mustard for salt stress tolerance at seedling stage - Ankit Dhillon,; Neeraj Kumar,; Manjeet Singh,; Jogender,; Annu,; Shreya, (Journal of Oilseed Brassica, 2025)
Salinity is a major limitation to the cultivation of Indian mustard, particularly during the seedling stage in salt-affected areas. Developing salt-tolerant lines through plant breeding, supported by germplasm screening and genetic variability assessments, is a key strategy to enable cultivation in these regions. This study aimed to evaluate salinity tolerance and assess the genetic variability among 48 genotypes of Indian mustard at the seedling stage. The genotypes were grown in a greenhouse under control conditions and subjected to 8 dSm-1 and 12 dSm-1 salt stress. A two-way analysis of variance revealed highly significant  (p≤0.01) effects of genotype, salinity level, and genotype x salinity interaction on most traits. Among the genotypes, RH 2066 and RH 0406 demonstrated a high degree of salt tolerance, comparable to known salinity-tolerant checks CS 52 and CS 58, at both stress levels based on morpho-physiological and biochemical parameters. Many traits, such as shoot length, root length, seedling length, fresh and dry weights, total soluble sugar content, and seedling vigour indices I and II, exhibited high genotypic and phenotypic variation. These traits also showed high broad-sense heritability and moderate to high genetic advance as a percentage of the mean, indicating their potential utility for breeding programs aimed at enhancing salinity tolerance in Indian mustard.